ANALISIS PENGARUH NON PERFORMING LOAN TERHADAP NILAI PERUSAHAAN DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL INTERVENING: (Studi pada Perusahaan Pembiayaan/Multifinance yang Terdaftar di Bursa Efek Indonesia Periode 2018-2022) - Putra, Irwansyah; Maisyarah, Renny; Purba, Rahima Br (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2024)
The study is specifically designed to empirically test the magnitude of the influence of Non-Performing Loans on Company Value with Good Corporate Governance as an intervening variable in Financing Companies/Multifinance Companies listed on the Indonesia Stock Exchange for the period 2018-2022. The population in this study consists of 15 financing sub-sector companies listed on the IDX for the period 2018-2022. By using purposive sampling, a sample of 12 companies with 5 years of observation was obtained, resulting in a total of 60 data points in this study. Classic assumption tests including normality and heteroscedasticity tests, estimation model selection including chow test, hausman test, and lagrange test, panel data regression analysis, goodness of fit tests including partial significance test (t-test), simultaneous significance test (f-test), and determination coefficient (R2), as well as path analysis to test hypotheses using Eviews 12 software. The results of the study indicate that Non-Performing Loans do not affect Good Corporate Governance in Financing Companies/Multifinance Companies listed on the Indonesia Stock Exchange for the period 2018-2022. Non-Performing Loans and Good Corporate Governance together influence Company Value in Financing Companies/Multifinance Companies listed on the Indonesia Stock Exchange for the period 2018-2022. Good Corporate Governance is unable to mediate the influence of Non-Performing Loans on Company Value in Financing Companies/Multifinance Companies listed on the Indonesia Stock Exchange for the period 2018-2022.